2014
DOI: 10.1371/journal.pone.0084758
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Assessment of Behavioral and Environmental Risk Factors for Lyme Disease Infection on Block Island, Rhode Island

Abstract: Peridomestic exposure to Borrelia burgdorferi-infected Ixodes scapularis nymphs is considered the dominant means of infection with black-legged tick-borne pathogens in the eastern United States. Population level studies have detected a positive association between the density of infected nymphs and Lyme disease incidence. At a finer spatial scale within endemic communities, studies have focused on individual level risk behaviors, without accounting for differences in peridomestic nymphal density. This study si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 49 publications
1
47
0
2
Order By: Relevance
“…Contrasting results were reported from other studies. Schwartz and Goldstein (1990) found no difference in self-reported quantitative tick exposure for B. burgdorferi seropositive versus seronegative outdoor workers; Klein et al (1996) found no difference among children with Lyme disease versus controls for the likelihood of deer ticks having been identified on the children; Smith et al (2001) found that those who reported discovering ticks on their person while checking had similar Lyme disease risk to those who reported never finding ticks while searching; and Finch et al (2014) found no difference between B. burgdorferi seropositive and seronegative persons in the proportion having experienced a tick bite within the past year (29 vs. 26% experiencing a tick bite). These contradictory findings may stem from: 1) variable accuracy in detecting tick bites across decades and in areas with different awareness of Lyme disease and vector ticks: 2) tick species identification not being done by entomologists in any of the eight above-mentioned studies; and 3) sample sizes that were not sufficiently large to overcome the low quality of data for self-reported tick bites.…”
Section: Risk Measures Based On Collection Of Ticks From Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrasting results were reported from other studies. Schwartz and Goldstein (1990) found no difference in self-reported quantitative tick exposure for B. burgdorferi seropositive versus seronegative outdoor workers; Klein et al (1996) found no difference among children with Lyme disease versus controls for the likelihood of deer ticks having been identified on the children; Smith et al (2001) found that those who reported discovering ticks on their person while checking had similar Lyme disease risk to those who reported never finding ticks while searching; and Finch et al (2014) found no difference between B. burgdorferi seropositive and seronegative persons in the proportion having experienced a tick bite within the past year (29 vs. 26% experiencing a tick bite). These contradictory findings may stem from: 1) variable accuracy in detecting tick bites across decades and in areas with different awareness of Lyme disease and vector ticks: 2) tick species identification not being done by entomologists in any of the eight above-mentioned studies; and 3) sample sizes that were not sufficiently large to overcome the low quality of data for self-reported tick bites.…”
Section: Risk Measures Based On Collection Of Ticks From Humansmentioning
confidence: 99%
“…However, most Lyme disease patients in the United States are unaware of a tick bite prior to symptom onset: the proportion of Lyme disease patients that remember a tick bite preceding their illness most commonly is in the range of 30–50% (Table 1). This finding implies: 1) that the majority of bites by I. scapularis ticks that result in transmission of B. burgdorferi go unnoticed; and 2) that the range of 10–37% of respondents, regardless of Lyme disease status, who report finding attached ticks over a preceding 12-mo period in Lyme disease endemic areas (Hanrahan et al 1984, Rand et al 1996, Burke et al 2005, Gould et al 2008, Finch et al 2014, Hook et al 2015) represents a gross underestimate of the true proportion of persons that experience tick bites annually.…”
Section: Risk Measures Based On Collection Of Ticks From Humansmentioning
confidence: 99%
“…Use of protective clothing that is sprayed or impregnated with diethyltoluamide (DEET), dimethyl phthalate, or permethrin is recommended for individuals who travel into the foliage of endemic areas. 43-44 A search for ticks should be carried out and the ticks removed as soon as possible. 44-45 Embedded ticks are best removed by use of tweezers to grasp the mouth parts without squeezing the body of the tick.…”
Section: Preventionmentioning
confidence: 99%
“…The risk of Lyme disease and presumably other tick borne diseases can be decreased by limiting the amount of edge between lawn and shrub on private properties. 43,46 Acaricide application to deer using a 4-poster device decreases the number of I. scapularis ticks. 47 Reduction in the number of deer on several islands has decreased both the number of I. scapularis ticks and the incidence of Lyme disease.…”
Section: Preventionmentioning
confidence: 99%
“…[119][120][121] Number of hours spent outdoors has a strong correlation with Lyme disease risk. 118,122,123 Protective clothing can protect from infection. Repellents, checking the body for ticks after outdoor activities, and showering within 2 hours of outdoor activities have consistently shown to be of benefit.…”
Section: Risk Factors For Lyme Diseasementioning
confidence: 99%